Mining of linear B cell epitopes of SARS-CoV-2 ORF8 protein from COVID-19 patients. Issue 1 (1st January 2021) - Wang, Xiaohui; Lam, Joy-Yan; Chen, Linlei; Au, Shannon Wing-Ngor; To, Kelvin K. W.; Yuen, Kwok-Yung; Kok, Kin-Hang
ABSTRACT: Given the on-going SARS-CoV-2 pandemic, identification of immunogenic targets against the viral protein will provide crucial advances towards the development of sensitive diagnostic tools and vaccination strategies. Our previous study has found that ORF8 protein of SARS-CoV-2 is highly immunogenic and shows high sensitivity in identifying COVID-19 disease. In this study, by employing overlapping linear peptides, we characterized the IgG immunodominant regions on SARS-CoV-2 ORF8 protein that are seropositive in the sera from SARS-CoV-2-infected patients. The major immunogenic epitopes are localized at (1) N-termini alpha helix, (2) the resides spanning beta 2 and 3 sheets, and (3) the loop between beta 4 and 5 sheets. Additionally, hamster model infected by SARS-CoV-2 further validates the seropositivity of the linear epitopes in vivo, demonstrating a potential application of the linear peptide-based immunization strategy. Taken together, identification and validation of these B-cell linear epitopes will provide insights into the design of serological diagnostics and peptide-based vaccination approach against this pandemic virus of high priority.